Wolf-Dietrich Niemeier. Das Orakelheiligtum des Apollon von Abai/Kalapodi. Eines der bedeutendsten griechischen Heiligtümer nach den Ergebnissen der neuen Ausgrabungen. - Donnellan, Lieve (Journal of Greek Archaeology, 2019)
Whereas one would usually not proceed with acquiring the booklet of a named public lecture, the present volume could be an exception, for it brings to the reader an excellent overview of the history and current state of the grossly overlooked Apollo sanctuary of Abae in Phocis. Wolf-Dietrich Niemeyer, director of the excavations at Abae since 2004, was invited to deliver the yearly Winckelmann lecture in Trier in 2013. His lecture includes a comprehensive overview of recent work done at the sanctuary, and presents some of the groundbreaking conclusions that can be drawn from it. None of the recent excavations have been fully published and even less is available in English, this despite the fact that Abae was one of the most important oracle sanctuaries of the ancient world.